2017
DOI: 10.1007/s12035-017-0584-5
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-Mediated Downregulation of miR-124 Activates Microglia by Targeting KLF4 and TLR4 Signaling

Abstract: Cocaine is known to activate microglia both in vitro and in vivo. High expression of microglial Toll-like receptors (TLRs) and their downstream signal transducers play critical roles in determining microglial activation status. Emerging reports have also demonstrated that cocaine can enhance the strength of TLR signaling. Detailed molecular mechanisms underlying this phenomenon, however, remain elusive. In this study, we investigated the role(s) of miR-124 in regulating microglial TLR4 signaling in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 68 publications
3
85
0
Order By: Relevance
“…Acute liver injury was significantly alleviated, and the survival rate of the mice increased. Studies have shown that SS can prevent the occurrence of D-GalN/ LPS-induced acute liver injury by regulating antiinflammatory and anti-apoptosis mechanisms [33,34], but the specific mechanism is unclear. Therefore, we further explored the protective mechanisms of SS extract on LPS and D-GalN-induced acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Acute liver injury was significantly alleviated, and the survival rate of the mice increased. Studies have shown that SS can prevent the occurrence of D-GalN/ LPS-induced acute liver injury by regulating antiinflammatory and anti-apoptosis mechanisms [33,34], but the specific mechanism is unclear. Therefore, we further explored the protective mechanisms of SS extract on LPS and D-GalN-induced acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant C57BL/6N mice were purchased from Charles River Laboratories (Wilmington, MA USA). Primary cultures of mouse mixed glia were prepared from the cerebral cortices of 1-to 3-d-old C57BL/6 newborn pups as described previously [88,89]. Briefly, cerebral cortices from neonatal mice were dissected and freed of meninges.…”
Section: Mpms Isolationmentioning
confidence: 99%
“…Primary microglia were obtained as previously reported [57,58]. Briefly, brains were removed from newborn mice (1-3 days old) and carefully cut into 0.5-1-mm 3 pieces.…”
Section: Cell Culture and Hypoxia Treatmentmentioning
confidence: 99%